HUMAN RESOURCE MANAGEMENT PRACTICES AND TURNOVER INTENTION AMONG HOTEL EMPLOYEES: THE ROLE OF PERSON-ORGANISATION FIT - Ag Budin, Dg Kamisah; Ambad, Sylvia Nabila Azwa (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2026)
Considering the negative consequences coming from employee turnover in the hospitality sector, a mediated model was suggested by this research that aimed to decrease turnover intention. Specifically, person-organization fit is advanced as a key mechanism through which human resource management practices may contribute to reducing employees’ intention to leave. Accordingly, the objectives of this study are threefold. The first objective is to evaluate the direct effect HRM practices have on staff turnover intention. Secondly, to examine the direct effect of HRM practices on person-organization fit. Finally, to evaluate the indirect effect of human resource management practices on turnover intention through person-organization fit. A questionnaire form was designed for Data collection and was distributed to a number of staff of three to five-star hotels in Kota Kinabalu, Sabah as a sample. Three hundred forms were distributed, and 214 were returned. Data analysis for this research was done by employing that showed considerable adverse impacts of compensation and career development on turnover intention. Moreover, compensation and career development significantly positively affects person-organization fit. Lastly, person-organization fit is mediating the connection between compensation and career development and turnover intention. The research suggests enhancement of compensation and career development because of its important impact on both person-environment fit and turnover intention.